Effectiveness of acupuncture intervention for neck pain caused by cervical spondylosis: study protocol for a randomized controlled trial - Que, Qinghui (BioMed Central, 2013)
BACKGROUND: Neck pain caused by cervical spondylosis has become a common health problem worldwide among >40-year-old adults. Acupuncture intervention is one of the most popular treatment measures for this disorder. However, evidence for its efficacy in relieving neck pain and recovering neck physiological function has not been established in randomized, placebo-controlled trials. The primary aim of this trial is to assess the efficacy and safety of active acupuncture compared with sham acupuncture intervention for neck pain caused by cervical spondylosis. METHODS/DESIGN: We will conduct a randomized, double-blind, parallel-group, placebo-controlled trial comparing active acupuncture with placebo (sham acupuncture). A total of 456 patients with neck pain caused by cervical spondylosis who meet the eligibility criteria from outpatient clinics of the Second People’s Hospital of Fujian Province and the Affiliated Rehabilitation Hospital, Fujian University of Traditional Chinese Medicine will be recruited and randomized into an active acupuncture or sham acupuncture group. The participants will undergo treatment sessions with either active or sham acupuncture intervention five times a week for 2 weeks. Evaluation by blinded assessors at baseline and at intervention for 1 and 2 weeks will include demographic characteristics, validated questionnaires (Northwick Park Neck Pain Questionnaire (NPQ) scale, Short-Form 36 (SF-36) scale, and McGill pain scale), examination of neck physiological function, and adverse events. All included patients will be followed up and investigated for relapse of neck pain at 4, 8, and 12 weeks after intervention. DISCUSSION: This paper describes the rationale and design of a randomized double-blind, placebo-controlled trial that aims to determine the efficacy and safety of acupuncture intervention for neck pain caused by cervical spondylosis. The primary outcomes are changes in the NPQ score and neck physiological function. Secondary outcome measures include quality of life, adverse events, and relapse of neck pain. If successful, this project will provide evidence of the efficacy and safety of acupuncture for neck pain caused by cervical spondylosis. TRIAL REGISTRATION: Chinese Clinical Trial Registry: ChiCTR-TRC-12002206. Registration date: 11 May 2012.